A Valuation Methodology And Pricing Analysis of Clickoptions - Quesney, Alexis (2007)
In the past twenty years, derivative finance has amazingly increased to become a core business in many banks and financial institutions. Until recent years, this development had only benefited to investors that had significant wealth, that is to say financial institutions and multinational corporations. Notwithstanding, things have changed and financial derivatives are now available to a great majority of investors, including private investors. This great progress has been achieved mostly thanks to binary betting (financial, sport, and political binary betting). This branch of finance has been first introduced in Anglo-Saxon countries.